조건부가치추정법을 이용한 도로의 경제가치 추정에 관한 실증적 연구 -수원시 47번 도로건설계획을 중심으로 - 박기학; Ki Hak Park (자원·환경경제연구, 2012)
본 연구는 주택의 자산가치, 즉 부동산 가격에서 ``도로``가 차지하는 금전적 가치를 추정해보고자, 최초 아파트 분양 시 시공사 또는 분양대행사(시행사)가 아파트 인근의 ``신 도로건설계획``을 가장 큰 호재(好材)라고 내세웠으나, 아파트 입주 후 도로건설계획이 전면 무산된 실제사례를 선정하여 ``도로``의 경제적 가치를 조건부가치추정법(CVM)을 활용한 지불의사금액 (WTP)으로써 살펴보았다. 따라서 본 연구에서 도출된 WTP는 ``신 도로건설계획`` 무산 전 · 후 1년 간(2010년 9월～2011년 9월)으로 국토해양부에서 고시한 해당 아파트의 가격 변동치와 ``부동산 114``에서 발표한 시세(市勢), 그리고 해당 아파트 입주민들이 주장하는 아파트의 자산가치 변화에 따른 체감(體感)을 비교한 실증적 사례이다. 본 연구 분석결과 입주민들의 WTP는 집값의 약 10%정도로 조사되었으며, 이는 같은 기간동안 국토해양부에서 고시한 아파트가격 변동폭(10% 하락)과는 유사한 수준으로 나타났다. 그러나 ``부동산 114``에서 발표한 아파트 실물 거래시장에서의 시세하락 폭은 이보다 훨씬 더 큰 것(24%)으로 나타났다. 이처럼 아파트 분양 시호재(好材)로 작용 할 것이라던 ``도로건설계획``의 무산에 따른 파급효과는 주민들이 느끼는 것보다 훨씬 더 심각하게 아파트 시세(市勢)에 영향을 미친다는 것을 짐작할 수 있었다. 이는 WTP와 관련된 주택의 특성과 조사변인들에 대한 상관관계 분석에서도 통계적으로 유의미한 것으로 나타났다. 따라서 주택 구매 시 ``도로``는 더이상 단순한 입지적 특성뿐만 아니라, 주택의 자산 가치를 결정하는 중요한 경제적 가치특성으로 평가되어야 할 것으로 사료되었다. The Purpose of this study was to assess the willingness to pay(WTP) for the new road construction plan(slip road of urban highway which was advertising extensively to reduce the time to the core of metropolitan area) on housing prices using contingent valuation method(CVM). And this study was an empirical study which was based on the consciousness of residents whose apartment was within the Suwon Si`s new plan of 47th road construction zone. In this study, it was revealed that the resident`s WTP for the plan of new road construction which was built on the neighborhood of apartment was within the 10 percent of housing prices that was similar to the standard declared price of MLTM(Ministry of Land, Transport and Maritime Affairs). And also revealed that the difference of sale prices of real estate company was 24 percent. The statistical assessment results show that both the resident`s characteristic variables such as gender, incomes, size of apartment and the accessability variables such as distance to parks, schools, department stores, living facilities were positive effects on the prices of apartments significantly. Finally, the house has depreciated than that of MLTM and WTO since torpedoed the road construction plan. These results imply that, we have to take capital appreciation of the property into account due to road construction since the accessibility was very significantly positive internal effects on the apartment housing prices.